(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Women are likely to attain empowerment when gender equality and justice are established, and women’s rights are acknowledged as human rights that are upheld. Conversely, justice and gender equality can only be realized in practice in daily life when women are really liberated. For the same, the study aimed to examine the influence of cultural, familial, and societal factors on the diverse struggles and milestones of women’s rights movements in 20th century India and to examine the effectiveness of constitutional provisions and special laws in improving the socio-economic status and protection of women’s rights in India. The study employed a qualitative research design to obtain secondary data which is then analyzed to unearth significant events in the women’s rights organizing in the 20th Century. The study used descriptive and explanatory research approaches to offer clear insight of the developments, challenges as well as resistance encountered by these movements. The major research finding of the study stated that the women’s rights movement of India during the twentieth century, acted based on the cultural, social and religious and family norms. Thus, despite numerous peculiarities of Indian nationalism, such as the prédominance of patriarchy and misogyny, women actively and effectively participated in the construction of public domain, or at least, in the struggle for the transformation of the existing structures.